2013
DOI: 10.3109/13561820.2013.784243
|View full text |Cite
|
Sign up to set email alerts
|

Team communications in surgery – creating a culture of safety

Abstract: As a key department within a healthcare organisation, the operating room is a hazardous environment, where the consequences of errors are high, despite the relatively low rates of occurrence. Team performance in surgery is increasingly being considered crucial for a culture of safety. The aim of this study was to describe team communication and the ways it fostered or threatened safety culture in surgery. Ethnography was used, and involved a 6-month fieldwork period of observation and 19 interviews with 24 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 38 publications
(41 reference statements)
3
104
0
3
Order By: Relevance
“…The theatre nurses may be reluctant to speak up about safety concerns and patient safety may be negatively affected (1). The hierarchy threatened safety because less powerful members had limited input in decision making, and were reluctant to speak up (15,33,39). In our study the theatre nurses feel they lose their concentration and focus when communication is not respectful in the team.…”
Section: Respectingmentioning
confidence: 80%
“…The theatre nurses may be reluctant to speak up about safety concerns and patient safety may be negatively affected (1). The hierarchy threatened safety because less powerful members had limited input in decision making, and were reluctant to speak up (15,33,39). In our study the theatre nurses feel they lose their concentration and focus when communication is not respectful in the team.…”
Section: Respectingmentioning
confidence: 80%
“…Operating theatre staff also implicated the ‘role of the institution’ in teamwork and communication. Perceived barriers to effective teamwork included a lack of ‘open communication’ and ‘dominance and hierarchy’54. Field notes of observed communication exchanges in the operating theatre showed themes such as ‘mimicry’ (for example, junior surgeons mimicking the behaviours of fellows and consultant), ‘withdrawal’ (typically juniors withdrawing from tense communication between other team members), and ‘association’ (attitudes towards a certain individual being extended to members of their professional subteam)54.…”
Section: Resultsmentioning
confidence: 99%
“…The frequent occurrence of behaviours such as ‘mimicry’ and ‘association’ substantiate this. Junior staff belonging to a specialty often mimic the negative teamwork behaviours of their seniors, and members of other specialties associate juniors with negative traits of seniors54. It appears challenging for individuals in theatre subteams adequately to assess themselves and their colleagues from other professions.…”
Section: Discussionmentioning
confidence: 99%
“…Common sense suggests that these activities necessitate recurring interaction between individuals. It has also been shown that a lack of face-to-face contact can lead to reduced trust and co-operation (Gillespie, Gwinner, Chaboyer & Fairweather, 2013 There are a number of limitations that must be taken into account in this study. The study is over five years old, thus some of the issues reported may have changed.…”
Section: The Impact Of Stability In Team Membership On Tpsmentioning
confidence: 99%